Attitudes and perceived barriers to firearm safety anticipatory guidance by pediatricians: a statewide perspective - Bijan Ketabchi; Michael A. Gittelman; Hayley Southworth; Melissa Wervey Arnold; Sarah A. Denny; Wendy J. Pomerantz (BMC, 2021)
Abstract Background Firearms are the second leading cause of injury-related death in American children. Safe storage of firearms is associated with a significantly decreased odds of firearm-related death, however more than half of US firearm owners store at least one firearm unlocked or accessible to a minor. While guidance by primary care providers has been shown to improve storage practices, firearm safety counseling occurs infrequently in the primary care setting. The primary objective of this study was to describe pediatricians' perceived barriers to providing firearm safety education to families in the pediatric primary care setting. Secondary objectives included identifying pediatric provider attitudes and current practices around firearm counseling. Methods This was a cross-sectional survey of pediatric primary care providers in Ohio. Participants were recruited from the Ohio AAP email list over a 3-month period. Only pediatric primary care providers in Ohio were included; subspecialists, residents and non-practicing physicians were excluded. Participants completed an anonymous online survey detailing practice patterns around and barriers to providing firearm safety counseling. Three follow-up emails were sent to pediatricians that failed to initially respond. Response frequencies were calculated using Microsoft Excel. Results Two hundred eighty-nine pediatricians completed the survey and 149 met inclusion criteria for analysis. One hundred seven (72%) respondents agreed that it is the responsibility of the pediatric primary care provider to discuss safe storage. Counseling, however, occurred infrequently with 119 (80%) of respondents performing firearm safety education at fewer than half of well child visits. The most commonly cited barriers to providing counseling were lack of time during office visits, lack of education and few resources to provide to families. A majority, 82 of pediatric providers (55%), agreed they would counsel more if given additional training, with 110 (74%) conveying they would distribute firearm safety devices to families if these were available in their practice. Conclusion Ohio pediatricians agree that it is the responsibility of the primary care provider to discuss firearm safety. However, counseling occurs infrequently in the primary care setting due to a lack of time, provider education and available resources. Improving access to resources for primary care pediatricians will be critical in helping educate families in order to protect their children through improved storage practices.